Combined Treatment with Systemic and Local Delivery of Substance P Coupled with Self-Assembled Peptides for a Hind Limb Ischemia Model - Kim, Ji Eun; Jung, Ki Moon; Kim, Soo Hyun; Jung, Youngmee (MARY ANN LIEBERT, INC, 2016)
When treating critical limb ischemia caused by various chronic diseases such as diabetes and hypertension, it is essential to effectively induce angiogenesis to supply blood flow to the ischemic region. Recently, several studies have investigated the effects of cell transplantation with mesenchymal stem cells (MSCs) as a therapeutic modality for treating these ischemic diseases. However, some limitations have to be overcome first before cell transplantation can be considered as a promising treatment for ischemic diseases, such as limited sources of cells and the low survival rates of transplanted cells. In this study, self-assembled peptide (SAP) hydrogels coupled with substance P (SP) were used to induce the recruitment of MSCs in an injury site in mouse ischemic hind limb models without exogenous injection of cells. In addition, a combined delivery strategy consisting of local and systemic delivery of SP was used to examine the synergetic effects of systemic and local deliveries. Limb ischemia in athymic mice was induced through the femoral artery by ligating and resecting its branches, and SAP coupled with SP (bioactive SAPs) was injected into the ischemic region. The therapeutic effects on the ischemic region were observed in terms of cell migration, fibrosis, apoptosis, and angiogenesis in each experimental group. The combined therapeutic delivery system resulted in the recruitment of more cells for effective regeneration, promotion of neovascularization, and formation of mature vessels for tissue perfusion and inhibition of fibrosis and cell apoptosis than a single treatment. In conclusion, it was confirmed that the combined therapy of local and system delivery of the SP-conjugated peptide hydrogels and SP could effectively enhance the mobilization of host cells related to angiogenesis to injured tissue, and consequently, they could be useful in treating ischemic diseases without cell transplantation.
Keywords: PERIPHERAL ARTERIAL-DISEASE; MESENCHYMAL STEM-CELLS; BONE-MARROW CELLS; THERAPEUTIC ANGIOGENESIS; NANOFIBERS; OSTEOARTHRITIS; IMPLANTATION; MOBILIZATION; PROGRESSION; ENHANCEMENT